La incidencia de los microcréditos en la producción agrícola de la parroquia San Luis, cantón Riobamba. - Coro Caicedo, Jairo Santiago (2025)
The following research aims to determine the impact of microcredit on tomate riñón agricultural production in San Luis parish, Riobamba canton. To this end, a quantitative approach was employed to collect specific about the characteristics of access to credit, production management, and the economic results achieved by farmers. The methodology applied included a budget analysis, along with a multiple linear regression model and surveys of 251 tomate riñón producers. Among the most relevant results, it was evident that producers have an average age of 49 years, showing that they are in a mature stage of their working life. On average, families have 2.84 children per family and 2.64 harvests per year, indicating that farmers in San Luis are taking advantage of intensive agricultural cycles. The average cultivated area is 0.248 hectares, equivalent to 2,480 square meters. It was also found that 92.83% of producers have employed technological innovations, such as greenhouses and drip irrigation systems, increasing average production to 23 kg/m². 71.71% of producers hire external labor, and 28.29% are hired by the producer and his or her family. Each producer employs an average of five workers, including family labor, with an average of four days of work per week, with pay of $15 per day of work, a minimum of $10 during the initial stage and a maximum of $20.00 at peak production. Barriers to financial access were also identified, with an average interest rate of 14.10% and farmers' limited ability to meet banking requirements. The study concludes that microcredit has had a positive impact on tomate riñón agricultural production, allowing producers to invest in infrastructure such as greenhouses and drip irrigation systems. Investments in technology, efficient use of resources, fertilizer acquisition, and machinery maintenance are key to increasing production and significantly improving crop quality. This research underscores the importance of strengthening financial inclusion policies and access to agricultural microcredit in rural communities.